Al Ikhtiyaajaat wa ad-Dawaafi’ Li asy-Syakhsiyyah ar-Roiisiyyah fi al-Qisshotaini al-Qoshiirotaini “Ash’udu Zaujaini” wa “Ana al-Maut” Li Taufiq al-Hakim (‘Ilmu an-Nafsi al-Adabi Li Henry Murray) - Raenza Agung Pratama (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The short story entitled